2020
DOI: 10.3390/ijms21061920
|View full text |Cite
|
Sign up to set email alerts
|

From Classical Laboratory Parameters to Novel Biomarkers for the Diagnosis of Venous Thrombosis

Abstract: Venous thrombosis is a common and potentially fatal disease, because of its high morbidity and mortality, especially in hospitalized patients. To establish the diagnosis of venous thrombosis, in the last years, a multi-modality approach that involves not only imaging modalities but also serology has been evolving. Multiple studies have demonstrated the use of some biomarkers, such as D-dimer, selectins, microparticles or inflammatory cytokines, for the diagnosis and treatment of venous thrombosis, but there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 141 publications
0
26
0
2
Order By: Relevance
“…Of note, decreased concentration of adiponectin and enhanced generation of plasma thrombin independently increase CVD risk [ 62 ]. Thrombin, by favoring clot formation, is linked to an increased risk of thromboembolic events [ 63 ].…”
Section: An Insight Into Other Implications Of Hypertriglyceridemia Beyond Atherosclerosismentioning
confidence: 99%
“…Of note, decreased concentration of adiponectin and enhanced generation of plasma thrombin independently increase CVD risk [ 62 ]. Thrombin, by favoring clot formation, is linked to an increased risk of thromboembolic events [ 63 ].…”
Section: An Insight Into Other Implications Of Hypertriglyceridemia Beyond Atherosclerosismentioning
confidence: 99%
“…Considering that there is a poor standardization of analytical methods for MP detection [ 76 ], there is a discrepancy between the results of different studies. Many of them, including a recent meta-analysis [ 77 ], linked elevated levels of MP with the future occurrence of thrombosis, whereas others did not demonstrate its role as a predictive biomarker [ 78 ] or showed heterogeneous results. An association with the occurrence of VTE in pancreatic cancer might be present, whereas in other cancer entities, this could not be confirmed [ 75 , 79 ].…”
Section: Inflammatory Biomarkers In Vtementioning
confidence: 99%
“…Several studies emphasize the role of inflammatory markers such as interleukin (IL)-1, 6, 8, and 10 in VTE. By influencing the expression of TF, inflammatory cytokines provide a trigger that may lead to thrombotic disease [ 78 ]. Genetic association studies have reported possible links between inflammation-related genetic variants, especially cytokines (e.g., IL-1, IL-4, IL-10) [ 81 ] and VTE, thus establishing a role of genetic background in predisposition to VTE and variable inflammatory processes in individuals.…”
Section: Inflammatory Biomarkers In Vtementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, search for specific biomarkers is necessary for both verification of the diagnosis and, importantly, prediction of the probability of thrombosis. A review by Anghel et al in this issue Journal presents a set of previously known as well as novel biomarkers of venous thrombosis and discusses their potential benefits and limitations in diagnosis and building the treatments strategy for DVT [ 3 ].…”
mentioning
confidence: 99%